Focus Measure In A Liquid-filled Diaphragm (LFD) Lens Using Passive Auto-focus Method. - Abdullah, S.J.; Ratnam, M.M.; Samad, Z (2010)
Auto-focusing in imaging systems depends on the determination of the correct image focus criterion.